Investigation of the Mathematical Connection Self-Efficacies of Pre-Service Teachers: A Quantitative Study From Turkey - Bodur, Ayşe Tuğçe; Ürek, Handan; Kobak Demir, Mevhibe (Pedagogika, 2024)
This study aims to examine the mathematical connection self-efficacy beliefs of pre-service teachers who were studying at the primary mathematics, secondary mathematics, and science teaching programs of a state university in Turkey. Data were collected through survey research and analyzed quantitatively. The results show no significant differences in the total beliefs based on gender, and undergraduate program. On the other hand, grade levels were found to be effective in this context.